Holocaust graphic narratives : generation, trauma, and memory - Aarons, Victoria (Rutgers University Press, 2020)
Introduction: Holocaust graphic narratives: visual testimonies of memory -- The performance of memory: Miriam Katin's we are on our own -- A child survivor's (auto) biographical memoir -- Memory frames: Mendel's daughter, a second-generation perspective -- "Replacing absence with memory": Bernice Eisenstein's graphic memoir -- I was the child of Holocaust survivors -- Flying couch: a third-generation tapestry of memory -- Yossel: April 19, 1943: possible histories -- Visual landscapes of memory: fracturing time and space -- Epilogue: an inheritance of memory.